Examining the Effects of Minimum Wage Levels, Human Development, and Population Growth on the Open Unemployment Rate in Banten - Sonia Putri; Marseto (Indonesian Journal Publisher, 2026)
This research was conducted to examine how minimum wage levels, the Human Development Index (HDI), and population growth contribute to changes in the open unemployment rate in Banten Province during 2010–2024. A quantitative framework was applied by utilizing secondary time-series data sourced from the Central Statistics Agency (BPS). The study employed multiple linear regression analysis supported by classical assumption tests, along with hypothesis evaluation through t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that, individually, minimum wage does not demonstrate a statistically significant relationship with open unemployment. In contrast, HDI shows a significant inverse relationship, while population growth is proven to significantly increase unemployment levels. When assessed collectively, all independent variables significantly influence the open unemployment rate. The model’s R-Squared value of 0.751215 suggests that 75.12% of fluctuations in unemployment are accounted for by the variables included in the model, whereas the remaining proportion is associated with external factors beyond this research scope. These results emphasize that labor quality improvement and population dynamics are key elements affecting unemployment, highlighting the importance of policy strategies that extend beyond wage regulation toward strengthening workforce capacity and expanding employment opportunities.